2012
DOI: 10.5539/ijbm.v7n16p118
|View full text |Cite
|
Sign up to set email alerts
|

The Key Reasons for Cross - Listing in East African Stock Exchanges by Firms Listed in the Nairobi Securities Exchange

Abstract: The purpose of this study was to investigate the key reasons behind the decision by the firm management of Nairobi Securities Exchange (NSE) listed firms to cross-list in East African Exchanges. The study employed a descriptive research design. A Likert type questionnaire was administered to the Chief Executive Officers (CEOs) or the Chief Financial Officers (CFOs) of the target firms. The study conducted factor analysis to identify the key reasons for the cross-listing in the East African region. The key reas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Findings from Outa (2011) indicate that IFRS adoption for NSE listed firms only marginally increased the accounting quality and even decreased the accounting quality of these firms. Waweru et al (2012) found that cross listed companies were valued higher than their domestic counterparts. Onyuma et al (2012) found that cross listing highly boosted investor confidence in East Africa.…”
Section: Research Problemmentioning
confidence: 99%
“…Findings from Outa (2011) indicate that IFRS adoption for NSE listed firms only marginally increased the accounting quality and even decreased the accounting quality of these firms. Waweru et al (2012) found that cross listed companies were valued higher than their domestic counterparts. Onyuma et al (2012) found that cross listing highly boosted investor confidence in East Africa.…”
Section: Research Problemmentioning
confidence: 99%
“…Following the same line of thought, Lin (2011) highlights the various benefits associated with exchange listing, which potentially outweigh the compliance costs. Additionally, Waweru, Pokhariyal and Mwaura (2012) in a descriptive research design, find that the key reasons for cross-listing are: investor recognition, expansion of business, the boost in shares, and the desire to lower the cost of capital. Beyond these strategic issues, from the financial standpoint there has been a large body of research regarding how cross-listing impacts the stock price on different dimensions.…”
Section: Introductionmentioning
confidence: 99%